Features of construction of a measuring rotation devices cell for measurement viscosity - А. А. Smirnykh (Тонкие химические технологии)
With the purpose of research of the phenomena taking place of the initial stage of process proposed the new original construction of measuring system rotational viscousimetr. The area of possible application modernized viscousimetr devices is expanded.